O nowy kształt finansów publicznych w Polsce. Zarys koncepcji - Komar, Andrzej (Wydział Prawa i Administracji UAM, 1989)
The economic, political and social changes which nowadays take part in Poland are not without effect on a future shape of public finances. The article attempts to sketch a conception of future public finances. The author starts with the assumption that it is indispensable to remodel them in the way which would reflect a limited role of the State in economic and financial processes. According to the author the care of public finances should be the budget, yet its organizational structure should be subject to reforms. The budgets of territorial self-governments should operate along the State budget, with functional ties between those budgets in the form of transfers of payments. Also the tax system needs a reform. In future, its basic elements will be income tax and value added tax. The author devotes much space to the conception of income tax. As to corporate finances, in consequence of retprivatization they should be eliminated from public finances. State enterprises would then operate in the spheres of municipal activity and higher public utility. Reformed in this way, they could be included into State or territorial budgets. The author is of the opinion that only the autonomous central bank, equipped with the monopoly of emission, should be included into public finances. Other banks should be in private or cooperative hands. Insurance companies should also be excluded from public finances. The author suggests that the scope of financial activity of the State and the range of public finances should be reduced to the budget, the taxes and the autonomous central bank.
For a new shape of public finances in Poland